Yield advantage, reciprosity functions and energy budgeting of lentil (Lens culinaris) + oat (Avena sativa) intercropping under varying row ratio and phosphorus management - SINGH, UMMED; SINGH, S R; SAAD, A A; KHANDAY, B A; SINGH, J K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during winter (rabi) seasons of 2006–08 at Sopore to evaluate the production potential, biological feasibility, economic viability and energy efficiency of intercropping of lentil (Lens culinaris Medikus) with oat (Avena sativa L.) under varying row ratio, P levels and biofertilizers. Oat was found dominant and aggressive as compared to lentil. Lentil and oat under 2:1 row ratio proved more remunerative and recorded higher yield advantage than 3:1 and 1:1 as judged by lentil-equivalent yield (1.13 tonnes/ha), crop productivity (4.77 kg/ha/ day), land-equivalent ratio (1.35), income-equivalent ratio (1.27), crop profitability (` 96.34/ha/day), area-time equivalent ratio (1.20), monetary advantage (` 8 580), net return (` 22 833/ha), biological efficiency, water-use efficiency (5.76 kg/ha-cm), P uptake (22.5 kg/ha) and energy productivity (739.3 g/MJ). Application of 17.2 kg P/ha recorded markedly higher lentil-equivalent yield, competition functions, water use, economics and energetics compared with rest of the treatments. Dual inoculation of lentil and oat seed with phosphorus solubilising bacteria +vasicular arbuscular mycorrhizae also showed significantly higher lentil-equivalent yield (1.18 tonnes/ha), yield attributes and other parameters, like biological efficiency, P uptake, water use, economic advantage and energy efficiency over seed inoculation with phosphorus-solubilizing bacteria or vasicular arbuscular mycorrhizae alone.